Greatness Engendered George Eliot and Virginia Woolf - Booth, Alison (Cornell University Press, 2018)
The egotism that fuels the desire for greatness has been associated exclusively with men, according to one feminist view; yet many women cannot suppress the need to strive for greatness. In this forceful and compelling book, Alison Booth traces through the novels, essays, and other writings of George Eliot and Virginia Woolf radically conflicting attitudes on the part of each toward the possibility of feminine greatness. Examining the achievements of Eliot and Woolf in their social contexts, she provides a challenging model of feminist historical criticism.The egotism that fuels the desire for greatness has been associated exclusively with men, according to one feminist view; yet many women cannot suppress the need to strive for greatness. In this forceful and compelling book, Alison Booth traces through the novels, essays, and other writings of George Eliot and Virginia Woolf radically conflicting attitudes on the part of each toward the possibility of feminine greatness. Examining the achievements of Eliot and Woolf in their social contexts, she provides a challenging model of feminist historical criticism.